Multiple calcifications within the parotid gland of patients with Sjögren's syndrome. Issue 1 (1st June 2012) - Izumi, Masahiro; Kise, Yoshiaki; Murata, Keiko; Murata, Atsushi; Nakayama, Miwa; Ariji, Yoshiko; Naitoh, Munetaka; Ariji, Eiichiro
Abstract: Purpose: The purpose of this study was to investigate computed tomography (CT) and clinical features relating to calcifications within the parotid gland of patients with Sjögren's syndrome (SS). Methods: Data from 30 patients with SS who had been examined by CT were extracted from our radiological information database accumulated from 2001 to 2011, and their CT images were reread carefully. Of these patients, 14 (all female; age range 20–95 years; mean age 61.4 years) with calcifications within the parotid gland were retrospectively investigated with CT findings. The relationship between calcification occurrence and clinical symptoms including parotid swelling and/or saliva colic was investigated. The degree of destruction of the parotid gland on CT images was also evaluated. Results: All calcifications of 14 patients were located within the parotid gland, not in the parotid duct. CT images of all calcifications showed small and regular round shapes. Multiple occurrences of calcifications were recognized in 10 patients, and a solitary occurrence was seen in 4 patients. Seven patients had bilateral calcifications. There was little relationship between the occurrence of calcifications and clinical symptoms, and the severity of destruction of the parotid gland. Conclusion: The presented CT and clinical features would be peculiar to SS because too many patients lacked the typical features of sialoliths within the parotid gland.